Natural Disasters and the Dynamics of Intangible Assets - López, Ramón (2012)
Empirical evidence suggests that the higher-order effects of natural disasters, which affect intangible assets, may be even more important than the material inter-industry effects. However, most existing general equilibrium models ignore higher order effects concerning human capital. Moreover, it is recognized that natural resource dependence increases vulnerability to natural disasters. Recent studies have indeed shown the potential importance of subsistence traps caused by asset losses in low-income economies from a partial equilibrium perspective. This paper presents an analysis that allows for endogenous investments in real assets (physical capital) as well as in human capital, explicitly considering the potential for subsistence traps arising from minimum consumption and minimum natural resource irreversibility thresholds. The general equilibrium ramifications of subsistence traps are developed. The main issue is that the economy may be subject to hysteresis: A temporary shock such as a natural disaster may leave permanent consequences for the economy. An obvious permanent effect of a one-time disaster shock is that physical man-made and natural assets owned especially by poor households may end up completely wiped out. The disaster may not be the direct cause; it may be that poor households would have to obtain minimum subsistence consumption out of depleted assets. However, not all permanent effects of a one-time shock are negative. Under certain conditions, the destruction of man-made physical and natural capital may have general equilibrium effects that increase the incentives to invest in human capital and may even propel a formerly stagnating economy into a virtuous path of continuing growth.